Women's portrayal in Indonesia popular film - Budiana, Daniel (Penerbit Universiti Kebangsaan Malaysia, 2024)
The portrayal of women has long been a concern, especially in cinema, including Indonesian cinema. The modern era of Indonesian cinema began in 1998 and continues to the present day, as the best period for Indonesian cinema. In 1998, only five films were produced, but production gradually increased until its peak in 2016, with 124 titles being produced. This growth has had a positive impact on the image of women in cinema, but it has also presented different values regarding the portrayal of women. This paper examines the portrayal of women characters in Indonesia's popular films, focusing on the top three best selling films. Using the textual analysis method, the study reveals that women are often portrayed in relation to stereotypes entrenched in patriarchal culture. Men still have a strong image as the provider and women are dependent objects. The findings also show that social values are the primary determinants of women's portrayal in film. For instance, in appearance, a good girl is appropriately dressed, will be saved and happy. In contrast, aggressiveness for women will lead them into destruction. The portrayal of women in Indonesian best seller movies cannot be separated from patriarchal and social values, which implies that these films not only reflect but also potentially reinforce and perpetuate existing gender norms and power dynamics within society. This suggests that the representation of women in such media plays a significant role in shaping public perceptions of gender roles, further embedding these values into the cultural fabric and potentially influencing the way women are treated and perceived in real life.